2004
DOI: 10.1128/jcm.42.3.1042-1047.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification ofYersinia enterocoliticain Pork Samples by a Novel Sample Preparation Method, Flotation, Prior to Real-Time PCR

Abstract: The development of real-time PCR thermal cycles in the late 1990s has opened up the possibility of accurate quantification of microorganisms in clinical, environmental, and food samples. However, a lack of suitable sample preparation methods that allow rapid quantification of the nucleic acids, remove PCR inhibitors, and prevent false-positive results due to DNA originating from dead cells has limited the use of quantitative PCR. We have used for the first time a new variant of density gradient centrifugation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
54
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 26 publications
1
54
1
1
Order By: Relevance
“…Real-time PCR technology enables quantification of microorganisms (9,16). An association between disease severity/mortality and bacterial DNA load measured by quantitative real-time PCR has been demonstrated for Neisseria meningitidis and Staphylococcus aureus infections (2, 6), but there has been no such study reported for patients with Vibrio septicemia.…”
mentioning
confidence: 99%
“…Real-time PCR technology enables quantification of microorganisms (9,16). An association between disease severity/mortality and bacterial DNA load measured by quantitative real-time PCR has been demonstrated for Neisseria meningitidis and Staphylococcus aureus infections (2, 6), but there has been no such study reported for patients with Vibrio septicemia.…”
mentioning
confidence: 99%
“…Flotation of oocysts was used to concentrate oocysts in the upper fluid portion and thereby reduce the amount of potential PCR inhibitors found in feces. 29 The flotate was used for coprologic detection of T. gondii by microscopy, bioassay, and copro-PCR. Prior to oocyst flotation, fecal samples were washed repeatedly with double-distilled water.…”
mentioning
confidence: 99%
“…Below concentrations of approximately 10 3 cells/ g of feces, the qPCR could detect the presence of L. intracellularis but could not quantify the concentration accurately or precisely, a finding that is common to qPCR studies. 5,19 Fecal samples 2-5 had apparent recovery rates ranging from 7% to 9%. The aspA qPCR product had the same specific melting temperature (Tm) peak of 79uC when amplified from all 5 fecal samples, although fecal sample 1, with low concentrations of L. intracellularis, had a second peak at a higher and incorrect Tm (Fig.…”
mentioning
confidence: 99%